Handbuch für Mobilitätserhebungen. KOMOD - Konzeptstudie Mobilitätsdaten Österreichs. - (:unkn) unknown (My University, 2011)
Recently several projects on behalf of ne Federal Department of Transport, Building and Housing (DOT) have been implemented to improve the availability of data describing the transportation sector. The survey MOBILITY IN GERMANY 2002 measured the day-to-day travel behaviour of the German population, simiar National Travel Surveys, then entitled "KONTIV", were carried out in 1976, 1982 and 1989. The data compiled in the course of this survey will be used both as a basis for transport planning in Germany and for scientific research on mobility. The "infas-lnstitut für angewandte Sozialwissenschaft Bonn" and "DIW Berlin" have been assigned by the Federal DOT to implement the survey. The genesis of this research was described here recently (pilot study, main survey design). In the paper we report on the population register based sample, the mixed mode survey, the contents of the collected data and other relevant aspects of the design and on the field results. Finally we inform about the availability of the project documentation and the generated micro-data. difu
Keywords: Mobilität; Verkehr; Verkehrsverhalten; Fahrradverkehr; Mobilitätsverhalten; Verkehrserhebung; Erhebungsverfahren; Methodenanwendung